Rural generalist nurses' perceptions of the effectiveness of their therapeutic interventions for patients with mental illness - Clark, Chanelle; Parker, Elizabeth; Gould, Trish (The Australian journal of rural health, 2005)
Objective:  To explore generalist nurses’ perceptions of their efficacy in caring for mentally ill clients in rural and remote settings, and their educational needs in the area of mental health care. Design:  A self‐administered questionnaire adapted from the Mental Health Problems Perception Questionnaire; a Likert scale used to rate the perceptions of nursing staff of their own ability to adequately treat and care for patients experiencing mental illness. Setting:  The Roma and Charleville Health Service Districts, Queensland, Australia. Subjects:  Nurses (Registered Nurses, Assistants in Nursing and Enrolled Nurses) in the Roma and Charleville health service districts (n = 163). Main outcome measures:  Generalist nurses’ perceptions regarding their therapeutic commitment, role competency and role support. Results:  Seventy per cent of respondents indicated that limited knowledge of mental health problems was an issue preventing nursing staff in rural and remote settings from providing optimum care to patients with mental illness. Twenty‐nine per cent of respondents indicated that they had never received or undertaken training or education in relation to the care, treatment or assessment of patients with mental illness. Conclusion:  Rural nurses do not feel competent, nor adequately supported, to deal with patients with mental health problems. In addition, the nurses’ education and ongoing training do not adequately prepare them for this sphere.